The karst and palaeokarst of North and North-East Greenland – physical records of cryptic geological intervals - Smith, P; Moseley, G (Geological Survey of Denmark and Greenland, 2022)
Carbonate rocks of Neoproterozoic to Silurian age are abundantly distributed around the coasts of North and North-East Greenland. Palaeokarst horizons are particularly well developed within the Portfjeld Formation (Ediacaran – earliest Cambrian) and beneath the Buen Formation (Cambrian Series 2), and there are caves within Ordovician limestones infilled by Caledonian molasse of Middle Devonian age. The youngest karst is a series of caves distributed from Hall Land in western North Greenland to Kronprins Christian Land in eastern North Greenland. Caves within Ordovician carbonates in Freuchen Land are currently the northernmost documented karst caves globally. The caves are mainly open phreatic conduits, any fill that is present is unlithified, and cave collapse is limited to minor breakdown associated with frost shattering. These geologically young caves are consistently located up to a few 100 m beneath the distinctive plateau that characterises the topography of the northern coast, and their identical context suggests that they developed in a single phase of speleogenesis. The caves are exposed where the plateau has been incised by outlet glaciers from the Greenland ice sheet. The timing of cave development in North Greenland is constrained by the mid- to late-Miocene (15–5 Ma) uplift of the plateau surface and the onset of fjord-forming glaciation in the latest Pliocene – earliest Pleistocene (c. 2.7–2.5 Ma). The evidence suggests that phreatic caves in the southern part of North-East Greenland, on C. H. Ostenfeld Nunatak, are of a broadly similar age. The caves of North and North-East Greenland offer a glimpse of large-scale phreatic drainage systems that developed below an uplifted coastal peneplain during Neogene time. They preserve an important part of the geological history of North and North-East Greenland that is otherwise absent from the physical geological record.